Differences in Eye Health, Access to Eye Care Specialists and Use of Lenses among Immigrant and Native-Born Workers in Spain - Seguí-Crespo, Mar (Int J Environ Res Public Health, 2019)
Latin American immigrants make up 49% of the total immigrant population in Spain, yet little is known about their eye health. The aim of this study is to determine if there are differences in self-perceived eye health, access to eye care specialists, and use of lenses between a sample of Latin American immigrant workers from Colombia and Ecuador, and native-born workers in Spain. We used data from the PELFI cohort (Project for Longitudinal Studies of Immigrant Families). The sample consisted of 179 immigrant workers born in Colombia or Ecuador, and 83 Spanish-born workers. The outcome variables were self-perceived eye health, access to eye specialists, and use of lenses. A descriptive analysis of the sample was carried out, and the prevalence of the three outcome variables in immigrants and natives was calculated and adjusted for explanatory variables. Random effects logistic regression models examined eye health outcomes by workers’ country of birth. Immigrants are less likely to report poor self-perceived eye health than native-born (ORc 0.46; CI 95%, 0.22–0.96). Furthermore, they have less access to specialists (ORc 2.61; CI 95%, 1.32–5.15) and a higher probability of needing lenses but not having them (ORc 14.14; CI 95%, 1.77–112.69). This latter variable remained statistically significant after adjusting for covariates (ORa 34.05; CI 95%, 1.59–729.04). Latin American immigrants may not value the use of lenses, despite eye care specialists indicating that they need them. Eye health education is required to recognize the importance of using lenses according to their visual needs.